2017
DOI: 10.1140/epjc/s10052-017-5428-y
|View full text |Cite
|
Sign up to set email alerts
|

Bulk viscous matter and recent acceleration of the universe based on causal viscous theory

Abstract: The evolution of the bulk viscous matter dominated universe has been analysed using the full causal theory for the evolution of the viscous pressure in the context of the recent acceleration of the universe. The form of the viscosity is taken as ξ = αρ 1/2 . We obtained analytical solutions for the Hubble parameter and scale factor of the universe. The model parameters have been computed using the observational data. The evolution of the prominent cosmological parameters was obtained. The age of the universe f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 54 publications
2
48
0
1
Order By: Relevance
“…It has been argued that if cosmic fluid is not perfect but viscous, then its effective pressure, P + Π B may turn negative and change the solution of Einstein's equation, thereby affecting the cosmic evolution of the Universe, leading to an inflation like behaviour [9][10][11][12]. Similar arguments have been made in the context of currently observed cosmic acceleration [13][14][15][16]. It have been also shown that the bulk viscosity can unify the dark sectors.…”
Section: Several Other Independent Observations Such As Baryon Acoustmentioning
confidence: 79%
“…It has been argued that if cosmic fluid is not perfect but viscous, then its effective pressure, P + Π B may turn negative and change the solution of Einstein's equation, thereby affecting the cosmic evolution of the Universe, leading to an inflation like behaviour [9][10][11][12]. Similar arguments have been made in the context of currently observed cosmic acceleration [13][14][15][16]. It have been also shown that the bulk viscosity can unify the dark sectors.…”
Section: Several Other Independent Observations Such As Baryon Acoustmentioning
confidence: 79%
“…Our novel solution generalizes the exact solution found in [17], for the particular values s = 1/2, γ = 1, where the expression τ = ξ/ρ for the relaxation time was used. In this article, the solution displays a decelerated phase an exponential expansion for late times, corresponding to a de Sitter phase.…”
Section: Introductionmentioning
confidence: 74%
“…In the above equations q 0 is the deceleration parameter at the present time t = t 0 , and the conditions a 0 = 1 and C 1 + C 2 = 1 have been set. This solution was previously found and discussed in [17], but with a particular relation for the relaxation time of the form ξ 0 ρ s−1 (which correspond to α = ξ 0 for our), instead of the more general relation as Eq. ( 7), in which the causality condition 0 < ≤ 1 is imposed.…”
Section: The Particular Case γ =mentioning
confidence: 83%
“…It is worthy to mention that if we consider the limit case ω = 0 in the differential equation written in (5), we obtain the non-relativistic or DM case (γ = 1) explored in Ref. [30].…”
Section: Preliminaries Of the Israel-stewart Theorymentioning
confidence: 91%